Exploratory behavior undergoes genotype–age interactions in a wild bird. Issue 16 (31st July 2019) - Class, Barbara; Brommer, Jon E.; van Oers, Kees
Abstract: Animal personality traits are often heritable and plastic at the same time. Indeed, behaviors that reflect an individual's personality can respond to environmental factors or change with age. To date, little is known regarding personality changes during a wild animals' lifetime and even less about stability in heritability of behavior across ages. In this study, we investigated age‐related changes in the mean and in the additive genetic variance of exploratory behavior, a commonly used measure of animal personality, in a wild population of great tits. Heritability of exploration is reduced in adults compared to juveniles, with a low genetic correlation across these age classes. A random regression animal model confirmed the occurrence of genotype–age interactions (G×A) in exploration, causing a decrease in additive genetic variance before individuals become 1 year old, and a decline in cross‐age genetic correlations between young and increasingly old individuals. Of the few studies investigating G×A in behaviors, this study provides rare evidence for this phenomenon in an extensively studied behavior. We indeed demonstrate that heritability and cross‐age genetic correlations in this behavior are not stable over an individual's lifetime, which can affect its potential response to selection. Because G×A is likely to be common in behaviors and have consequences for our understanding of the evolution of animal personality, more attention should be turned to this phenomenon in the future work. Abstract : In this study, we show that heritability of exploratory behavior, a standard measure of animal personality, decreases with age in a wild population of great tits. Using a random regression animal model, we demonstrate that this age‐related decline in heritability is caused by a decrease in additive genetic variance and an increase in residual variance before individuals become 1 year old. This study constitutes rare evidence for genotype–age interaction (G×A) for an extensively studied behavior in a wild population. Because G×A is likely to be common and has profound evolutionary consequences, more attention should be turned to this phenomenon in the future work.